Diversity in Orthopaedic Surgery Medical Device Clinical Trials: An Analysis of the Food and Drug Administration Safety and Innovation Act. Issue 3 (1st February 2023) - Issa, Tariq Ziad; Lambrechts, Mark J.; Lin, Jasmine S.; Brush, Parker L.; Canseco, Jose A.; Hilibrand, Alan. S.; Kepler, Christopher K.; Schroeder, Gregory D.; Vaccaro, Alexander R.
Abstract : Introduction: Demographic factors contribute markedly to orthopaedic surgery outcomes. However, women and minorities have been historically excluded from clinical trials. The United States passed the Safety and Innovation Act (Food and Drug Administration Safety and Innovation Act [FDA-SIA]) in 2012 to increase study diversity and mandate reporting of certain demographics. The purpose of this study was to investigate demographic reporting and analysis among high-risk orthopaedic medical device trials and evaluate the effectiveness of the FDA-SIA in increasing diversity of study enrollment. Methods: The premarket approval database was queried for all original submissions approved by the Orthopedic Advisory Committee from January 1, 2003, to July 1, 2022. Study demographics were recorded. Weighted means of race, ethnicity, and sex were compared before and after FDA-SIA implementation with the US population. Results: We identified 51 orthopaedic trials with unique study data. Most Food and Drug Administration device trials reported age (98.0%) and sex (96.1%), but only 49.0% and 37.3% reported race and ethnicity, respectively. Only 23 studies analyzed sex, six analyzed race, and two analyzed ethnicity. Compared with the US population, participants were overwhelmingly White (91.36% vs. 61.63%, P < 0.001) with a significant underrepresentation of Black (3.65% vs. 12.41%, P = 0.008), Asian (0.86% vs. 4.8%, P = 0.030), and Hispanic participants (3.02% vs. 18.73%, P < 0.001) before 2013. The FDA-SIA increased female patient enrollment (58.99% vs. 47.96%, P = 0.021) but did not increase the enrollment of racial or ethnic minorities. Conclusion: Despite efforts to increase the generalizability of studies within the FDA-SIA, orthopaedic medical devices still fail to enroll diverse populations and provide demographic subgroup analysis. The study populations within these trials do not represent the populations for whom these devices will be indicated in the community. The federal government must play a stronger role in mandating study diversity, enforcing appropriate statistical analysis of the demographic subgroups, and executing measures to ensure compliance. Level of Evidence: I.